Efficient Achromatic Broadband Focusing and Polarization Manipulation of a Novel Designed Multifunctional Metasurface Zone Plate - Shaobo Ge; Weiguo Liu; Xueping Sun; Jin Zhang; Pengfei Yang; Yingxue Xi; Shun Zhou; Yechuan Zhu; Xinxin Pu (Nanomaterials, 2021)
In this paper, comprehensively utilizing the diffraction theory and electromagnetic resonance effect is creatively employed to design a multifunctional metasurface zone plate (MMZP) and achieve the control of polarization states, while maintaining a broadband achromatic converging property in a near-IR region. The MMZP consists of several rings with fixed width and varying heights; each ring has a number of nanofins (usually called meta-atoms). The numerical simulation method is used to analyze the intensity distribution and polarization state of the emergent light, and the results show that the designed MMZP can realize the polarization manipulation while keeping the broadband in focus. For a specific design wavelength (0.7 μm), the incident light can be converted from left circularly polarized light to right circularly polarized light after passing through the MMZP, and the focusing efficiency reaches above 35%, which is more than twice as much as reported in the literature. Moreover, the achromatic broadband focusing property of the MMZP is independent with the polarization state of the incident light. This approach broadens degrees of freedom in micro-nano optical design, and is expected to find applications in multifunctional focusing devices and polarization imaging.